Diagnostic Accuracy of Tuning Fork Tests for Hearing Loss: A Systematic Review. (17th April 2018) - Kelly, Elizabeth A.; Li, Bin; Adams, Meredith E.
Abstract : Objective: (1) To determine the diagnostic accuracy of tuning fork tests (TFTs; Weber and Rinne) for assessment of hearing loss as compared with standard audiometry. (2) To identify the audiometric threshold at which TFTs transition from normal to abnormal, thus indicating the presence of hearing loss. Data Sources: PubMed, Ovid Medline, EMBASE, Web of Science, Cochrane, and Scopus and manual bibliographic searches. Review Methods: A systematic review of studies reporting TFT accuracy was performed according to a standardized protocol. Two independent evaluators corroborated the extracted data and assessed risk of bias. Results: Seventeen studies with 3158 participants, including adults and children, met inclusion criteria. The sensitivity and specificity of the Rinne test for detecting conductive hearing loss ranged from 43% to 91% and 50% to 100%, respectively, for a 256‐Hz fork and from 16% to 87% and 55% to 100% for a 512‐Hz fork. The audiometric thresholds at which tests transition from normal to abnormal ranged from 13 to 40 dB of conductive hearing loss for the Rinne test and from 2.5 to 4 dB of asymmetry for the Weber test. Significant heterogeneity in TFT methods and audiometric thresholds to define hearing loss precluded meta‐analysis. There is high risk of bias in patient selection for a majority of the studies. Conclusion: Variability exists in the reported test accuracy measurements of TFTs for clinical screening, surgical candidacy assessments, and estimation of hearing loss severity. Clinicians should remain mindful of these differences and optimize these techniques in specific clinical applications to improve TFT accuracy.